2017
DOI: 10.1002/jwmg.21218
|View full text |Cite
|
Sign up to set email alerts
|

Spatial ecology and habitat selection of eastern hognose snakes

Abstract: The eastern hognose snake (Heterodon platirhinos) is a species of conservation concern, especially in the northeastern portion of its range. They remain relatively common at Cape Cod National Seashore, Barnstable County, Massachusetts, USA, where we studied their spatial ecology and habitat selection. We radio‐tracked 17 adult snakes (10 F, 7 M) from May 2009 to November 2011, yielding 765 relocations. We conducted a use‐availability analysis to investigate patterns of microhabitat selection using a subset of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 66 publications
2
6
0
Order By: Relevance
“…The mean MCP home‐range area we calculated for eastern hog‐nosed snakes in Ontario (39 ha, n = 17 snakes) is comparable to most previously reported values for populations in the northeastern United States: 52 ha (LaGory et al 2009), 35 ha (Buchanan et al 2017), 25 ha (Vanek and Wasko 2017), and 19 ha (Akresh et al 2017). Goulet et al (2015) reported larger home ranges, averaging 73 ha, in New Hampshire.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The mean MCP home‐range area we calculated for eastern hog‐nosed snakes in Ontario (39 ha, n = 17 snakes) is comparable to most previously reported values for populations in the northeastern United States: 52 ha (LaGory et al 2009), 35 ha (Buchanan et al 2017), 25 ha (Vanek and Wasko 2017), and 19 ha (Akresh et al 2017). Goulet et al (2015) reported larger home ranges, averaging 73 ha, in New Hampshire.…”
Section: Discussionsupporting
confidence: 86%
“…Construction of minimum convex polygons (MCPs) is the most common method to estimate home ranges (Hansteen et al 1997, Burgman and Fox 2003, Nilsen et al 2008) and is recommended for reptiles (Row and Blouin‐Demers 2006 b ). We calculated MCPs for snakes with ≥15 telemetry locations as recommended by others (LaGory et al 2009, Akresh et al 2017, Buchanan et al 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also revealed that snakes avoided bare ground ( Sperry et al, 2009 ; Baxley, Lipps & Qualls, 2011 ; Gardiner et al, 2015 ). Leaf litter cover can keep the ground temperature relatively stable and provide conditions for thermoregulation ( Buchanan et al, 2017 ). In areas of bare soil, the temperature changes greatly, which may exceed the tolerance limit of snakes.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a review of the current literature and data from our previous research (Fig. 2), we identified 11 important habitat variables for P. mangshanensis (Baxley, Lipps & Qualls, 2011;Gardiner et al, 2015;Buchanan et al, 2017;Sutton et al, 2017;Sprague & Bateman, 2018). Habitat variables were measured as follows.…”
Section: Habitat Variablesmentioning
confidence: 99%